Sosialisasi Pemanfaatan Media Sosial Sebagai Alternatif Metode Pembelajaran Guru Bahasa Indonesia Tingkat SMP di Kota Jambi - Rasdawita, Rasdawita; Nurfadilah, Nurfadilah; Rahmawati, Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This activity is a community service activity carried out at the Jambi City Education Office. Based on initial discussions and surveys, it is known that teachers find it difficult to build a learning climate that is familiar with technology. This is the reason this service activity is carried out. Teachers as educators can utilize various things to support learning. Along with technological developments, teachers are also expected to be able to utilize technology in the teaching and learning process. Through the service activities carried out, the service team provides outreach to teachers about utilizing social media in learning Indonesian. The service was held in the Tut Wuri Handayani Hall of the Jambi City Education Office and was attended by state and private middle school teachers. The team provided service material about the use of social media by accompanying simple practices in using Whatsapp and Instagram. The result of this activity is that middle school Indonesian language teachers in Jambi City received information related to the use of features in applications or social media platforms. Apart from that, teachers are also given counseling regarding wise use of social media so they can guide students in using social media in learning.